Repeated Application of Transcranial Diagnostic Ultrasound Towards the Visual Cortex Induced Illusory Visual Percepts in Healthy Participants - Schimek, Nels; Burke-Conte, Zeb; Abernethy, Justin; Schimek, Maren; Burke-Conte, Celeste; Bobola, Michael; Stocco, Andrea; Mourad, Pierre D. (Frontiers in Human Neuroscience, 2020)
Transcranial magnetic stimulation (TMS) of the visual cortex can induce phosphenes as can non-diagnostic ultrasound, the latter while participants have closed their eyes during Stimulation. Here we sought to study potential alteration of a visual target (a white crosshair) due to application of diagnostic ultrasound to the visual cortex. We applied a randomized series of actual or sham diagnostic ultrasound to the visual cortex of healthy participants while they stared at a visual target, with the ultrasound device placed where TMS elicited phosphenes. These participants observed percepts 7 out of 10 times, consisting of extra or extensions of lines relative to the original crosshair, and additional colors. Observation of a percept occurred an average of 53.7 +/- 2.6% of the time over the course of the experiment for these participants. In contrast, 7 out of 10 participants exposed to sham-only diagnostic ultrasound observed comparable percepts an average of 36.3 +/ 1.9% of the time, a statistically significant difference (p < 0.00001). Moreover, on average, participants exposed to a combination of sham and actual ultrasound reported a net increase of 47.9 percentage points in the likelihood that they would report a visual effect by the end of the experiment. Our experiment demonstrated that a random combination of sham-only and actual diagnostic ultrasound applied to the visual cortex of participants increased the likelihood that they would observe visual effects, but not the type of effects, with that likelihood increasing over the course of the experiment. From this we conclude that repeated exposures by diagnostic ultrasound made the visual cortex more responsive to stimulation of their visual cortex by the visual target. These observations, consistent with other’s observation of effects of diagnostic ultrasound stimulation of human motor cortex and amygdala, as well as the FDA approved nature of diagnostic ultrasound, may lead to increased study of diagnostic ultrasound applied to human brain.